Examination of Migraine Management in Emergency Departments - Satnam S Nijjar; Leah Pink; Allan S Gordon (Pain Research and Management, 2011)
BACKGROUND: Despite advances in treatment, patients with migraine have been underdiagnosed and undertreated, specifically in emergency departments. In addition, great variability exists with respect to the diagnosis, management and treatment of migraine patients in emergency departments. In particular, migraine-specific treatments, including serotonin receptor agonists, appear to be rarely used.